Unlocking the Shopper’s Mind: How Emerging Technologies Like Artificial Intelligence Is Shaping the Future of Retail - Florina-Gabriela MITU; Marius BOTA; Emil Emanuel SAVAN (Studia Universitatis Babeş-Bolyai Negotia)
The fast-changing landscape of consumer behavior, driven by digitalization in retail, fosters big changes in industry. Two other major trends are omnichannel strategies, integrating physical experience with online shopping, and the rise of experiential shopping technologies such as AR (augmented reality) in shaping how retailers connect with consumers. The increasing function of artificial intelligence and machine learning to optimize supply chains also raises crucial questions regarding the ethics of these developments in retail marketing. This paper also discusses neuromarketing, an innovative approach whereby neuroscience is combined with marketing, as a tool to help optimize sales techniques and improve customer service. Techniques such as EEG (electroencephalogram), eye-tracking, and fMRI (functional magnetic resonance imaging) offer retailers insight into customers’ unconscious responses to stimuli, from advertising to product placement. While these approaches have been increasingly adopted by retailers, the current study investigates whether the drift toward digital platforms impacts the efficiency of neuromarketing strategies and how AI takes further priority in this direction (Goncalves et al., 2024). The backbone of this research is to establish the level at which businesses have integrated neuromarketing into their greater marketing strategies and to find any new consumer behavior that could be proposed within a retail context. This paper will attempt to contribute, by exploratory research and secondary data analysis, to a better understanding of how these new trends adapts to the digitization of retail due to technological development and ethical concerns raised by its increased use.